Pilar Adón or the incursions of the lyric into the novel: "De bestias y aves" (2022) as an example of a lyrical novel. - Íñiguez Egido, Alain (Tropelías: Review of Literary Theory and Comparative Literature, 2023)
In the literary panorama of recent times, there are some proposals worthy of mention in a monograph about poetry due to the conjunction that they establish between different genres. Pilar Adón has been able to highlight the latter with the publication of her recent novel, De bestias y aves (2022). The analysis of those features that allow it to be framed within the genre of the lyrical novel provides the opportunity to underline the condition of a product derived from a literary production that, for the most part, sets aside the frontiers between literary genres. The use of natural space as a symbol, the thinning out of the plot and the dilation of time in the novel are some of the aspects discussed in this article that show the incursion of Adón's poetry into his latest novel, and which emphasise its status as a product that challenges realism in the current context of the novel.
Keywords: novel